MyShake Citizen Seismologists Help Launch Dual-Use Seismic Network in California - Strauss, Jennifer A.; Kong, Qingkai; Pothan, Sharon; Thompson, Stephen; Mejia, Ramon F.; Allen, Steven; Patel, Sarina; Allen, Richard M. (Frontiers in Communication, 2020)
The MyShake app began delivering earthquake early warning alerts to users in California on October 17, 2019. The app delivers alerts from ShakeAlert when the estimated magnitude is 4.5 or greater to phones in the Modified Mercali Intensity (MMI) III or greater zone. MyShake users receive the alerts, but also serve as citizen seismologists for the system. They contribute accelerometer data allowing this dual-use network to serve as an alert delivery platform and an earthquake monitoring network. Users are also now afforded the ability to interactively share their experience in an earthquake with others on the system through the use of an experience report. The design and maintenance of this system requires the interoperability of many technical systems (servers, code, smartphones) and stakeholders (scientists, federal and state agencies, public). This imparts some constraints on our ability to address problems and implement new features, but ultimately provides a considered framework within which we can design for future use cases. We discuss new features of the app, such as the experience report, the collection of timing information to improve delivery latencies, and examples of how human centered design responds to user needs. We also look at privacy considerations and ways MyShake can continue to improve in the future.